The Effect Of Profitability On Stock Prices In Companies Incorporated In The Lq45 Index On The Indonesia Stock Exchange - Lisda Yanti; Syamsu Alam; Andi Ratna Sari Dewi (Jurnal Mirai Management, 2023)
This research was conducted on companies incorporated in the LQ45 index on the Indonesia Stock Exchange in the 2016-2018 period. This study aims to determine the effect of ROA and ROE on stock prices, both partially and simultaneously. This type of research uses Secondary Data with a quantitative approach. The data collection technique uses documentation techniques sourced from the financial statements of LQ45 index companies for the period 2016-2018 obtained from the Indonesia Stock Exchange website. The population of this study is LQ45 index companies on the Indonesia Stock Exchange for the period 2016-2018. The sample in this study was obtained using Purposive Sampling Method, with a sample number of 30 LQ45 index companies. The analytical methods used in this study are multiple linear regression analysis methods, classical assumption tests, hypothesis tests, and determination coefficient tests using SPSS. The results found that: (1) ROA has a positive and significant effect on stock prices; (2) ROE has a positive and significant effect on stock prices; (3) ROA and ROE simultaneously have a significant effect on stock prices Keywords: Return on assets (ROA); Return on Equity (ROE); Stock Price